PENGARUH CORPORATE GOVERNANCE&KEPEMILIKAN KELUARGA TERHADAP NILAI PERUSAHAAN DENGAN TAX AVOIDANCE SEBAGAI VARIABEL INTERVENINGPADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Dewi Kusuma Wardani; Valentina Desi Wulandari (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to determine the effect of corporate governance & family ownership on firm value, tax avoidance on firm value, corporate governance on family ownership on tax avoidance. This study uses a population of manufacturing companies listed on the Indonesia Stock Exchange and sampling using the purpose sampling method. This study uses path analysis. The results of this study indicate that corporate governance & family ownership has a positive effect on firm value, tax avoidance has a negative effect on firm value, corporate governance & family ownership has no effect on tax avoidance. Corporate governance & family ownership affects the value of the company through tax avoidance